2015
DOI: 10.1016/j.actbio.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Localized delivery of dexamethasone-21-phosphate via microdialysis implants in rat induces M(GC) macrophage polarization and alters CCL2 concentrations

Abstract: Microdialysis sampling probes were implanted into the subcutaneous space on the dorsal side of male Sprague Dawley rats to locally deliver dexamethasone-21-phosphate (Dex) with the aim of altering in vivo macrophage polarization. Macrophage polarization is of significant interest in the field of biomaterials since wound healing macrophages are a possible means to extend implant life as well as improve tissue remodeling to an implant. Quantitative analysis of CCL2 in collected dialysates, gene expression and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 60 publications
(77 reference statements)
2
22
0
Order By: Relevance
“…Most work with Dex-releasing biomaterials uses standard histological, rather than molecular assessments, of implant/tissue outcomes. Our previous work has shown that Dex delivered immediately after microdialysis probe insertion is capable of shifting macrophages to a more CD163+ state, the former M2c designation [37]. This is consistent with other macrophage studies in rats with dexamethasone that have also targeted CD163+ cells [38].…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Most work with Dex-releasing biomaterials uses standard histological, rather than molecular assessments, of implant/tissue outcomes. Our previous work has shown that Dex delivered immediately after microdialysis probe insertion is capable of shifting macrophages to a more CD163+ state, the former M2c designation [37]. This is consistent with other macrophage studies in rats with dexamethasone that have also targeted CD163+ cells [38].…”
Section: Introductionsupporting
confidence: 85%
“…Similarly, we showed in a previous study that immediate and daily infusion of Dex to a subcutaneous wound site in rats, resulted in the significant decrease in IL-6 gene transcription [37]. It should also be noted that IL-6 is known to exhibit either pro- and anti-inflammatory properties [55].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…For example, microdialysis tubing might be used to control the timing of cytokine infusion into the site of a wound. Keeler et al 72 have used this strategy to deliver dexamethasone, which promotes M2c polarization and reduces fibrous encapsulation. Similarly, osmotic pumps have also been used to deliver IL4 to modulate M2a polarization and mitigate orthopedic implant wear particle-associated inflammation.…”
Section: Delivery Of Cytokines To Modulate Phenotype Of Endogenous Mamentioning
confidence: 99%